Tick-borne relapsing fever in Sabzevar (Khorasan Razavy Province), North-Eastern Iran (Bangladesh Journal of Medical Science, 2016)
Background: Soft ticks play an important role in transmission of bacteria, rikettsia and viral diseases to human. In Iran soft ticks of the genus Ornithodoros spread the tick-borne diseases.Objective: Present study was performed to investigate the latest situation of tick-borne relapsing fever (TBRF) among people and tick infectivity to Borrelia in Sabzevar, an endemic tick-borne relapsing fever region in Iran.Methodology: Ticks were collected in the sampled areas of Sabzevar County by clustered random sampling. The suspected cases of TBRF were passively detected in the study villages. Each of Ornitodoros tholozani was separately crushed and resultant homogenate was inoculated intraperitoneally into a white mouse.Results: A total of 3892 soft ticks were collected and identified. The Argas and Ornitodoros genus were observed 69.6 % and 30.4 %, respectively. Argas persicus, Ornitodoros lahorensis, O. tholozani and A. reflexus species were found 68.0 %, 25.6 %, 4.8% and 1.6 %, respectively. A. persicus (68.0 %) and A. reflexus were found as the highest and the lowest frequent species. Totally 5.2 % of O. tholozani ticks infected with Borrelia persica. Among individuals who suspected to the TBRF, 5 cases infected with B. persica.Conclusions: The vector infectivity rates were 5.2 % which can be an important factor and ability to make proper decide decision for better TBRF management and revision of control measures. Also this study raises our country TBRF epidemiological aspects and improves them.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.551-555